A cross sectional study to assess pharmacotherapeutic adherence among diabetes mellitus patients in tertiary care hospital - Gaur, Richa; Kushwaha, Virendra; Agrawal, Pooja; Agrawal, Saurabh; Kumar, Amit; Malhotra, Kriti (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes mellitus (DM) refers to a group of common metabolic disorders that associated with abnormalities in carbohydrate, fat, and protein metabolism which results in chronic complications. Attainment of optimal blood sugar level is generally based on appropriate usage and proper adherence to prescribed medications. The study was, therefore, aimed to assess adherence to oral antidiabetic drugs among diabetic patients attending outpatient clinic of L. L. R. Hospital, G.S.V.M. Medical College, Kanpur, U.P. Methods: Hospital based cross-sectional study design was conducted from April 2017 to June 2018. The data was collected by interviewing T2DM patients receiving antidiabetic medications using Morisky’s four item adherence assessment questionnaire. The collected data was processed and analyzed with SPSS version 20. Results: From the 126 patients of diabetes, when asked about adherence to their medications as per the Morisky's four item method, 114 (90.47%) of them did not forget to take the drugs, 108 (85.71%) of patients reported that they had been being careful in taking their medications, 90 (71.42%) patients did not stop medications when they felt better and the other 108 (85.71%) patients reported that they did not stop medications when they felt worse while taking medications. This study shows that 54 (42.86%) respondents were adherent to their medications. Conclusions: This study revealed a moderate level of adherence among the participants and statistically significantly depended upon their socioeconomic status. Efforts are needed to increase the medication adherence of these patients’, so they can realize the full advantage of prescribed therapies.